Detection of a Yersinia pestis gene homologue in rodent samples - Giles, Timothy A.; Greenwood, Alex D.; Tsangaras, Kyriakos; Giles, Tom C.; Barrow, Paul A.; Hannant, Duncan; Abu-Median, Abu-Bakr; Yon, Lisa (PeerJ, 2016)
A homologue to a widely used genetic marker, pla, for Yersinia pestis has been identified in tissue samples of two species of rat (Rattus rattus and Rattus norvegicus) and of mice (Mus musculus and Apodemus sylvaticus) using a microarray based platform to screen for zoonotic pathogens of interest. Samples were from urban locations in the UK (Liverpool) and Canada (Vancouver). The results indicate the presence of an unknown bacterium that shares a homologue for the pla gene of Yersinia pestis, so caution should be taken when using this gene as a diagnostic marker.
Keywords: Yersinia pestis; Rodents; Screening; Microarray